Control for active chilled beam for HVAC system - Mohamed Noor Hafiz Abdul Halim. (2013)
The chilled beam technology has been around for a long time. Originating from the Scandinavia, it has now covered most of Europe with its energy saving traits and now slowly spreading in the United States. The chilled beams operate on the basis of convection making use of the laws of thermodynamic to function. Even with the reduced usage of incoming outdoor air, chilled beam system is capable of meeting design requirement for cooling a conditioned space. In this paper, the functionality, system operation as well as its implementation will be further discussed.